Azaacenes bearing five-membered rings - Ganschow, Michael; Koser, Silke; Hodecker, Manuel; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
We report the synthesis of processible (dihydro)pyracyclene- and acenaphthylene-substituted azaacenes using condensation reactions in solution. The targets are characterized via cyclic voltammetry, X-ray crystallography, UV/Vis, fluorescence spectroscopy and DFT/NICS calculations. Formal hydrogenation of the annulated five-membered ring surprisingly alters emission in the solid-state as a consequence of modulation of aromaticity and HOMO-LUMO overlap. Five highly fluorescent, crystalline azaacenes were investigated as emitters in organic light-emitting diodes, and their performance with respect to luminance and efficiency was compared to that of structurally related azaacenes.